Tacrolimus Loaded Cationic Liposomes for Dry Eye Treatment - Chen, Xiang; Wu, Jicheng; Lin, Xueqi; Wu, Xingdi; Yu, Xuewen; Wang, Ben; Xu, Wen (Frontiers in Pharmacology, 2022)
Eye drops are ophthalmic formulations routinely used to treat dry eye. However, the low ocular bioavailability is an obvious drawback of eye drops owing to short ocular retention time and weak permeability of the cornea. Herein, to improve the ocular bioavailability of eye drops, a cationic liposome eye drop was constructed and used to treat dry eye. Tacrolimus liposomes exhibited a diameter of around 300 nm and a surface charge of +30 mV. Cationic liposomes could interact with the anionic ocular surface, extending the ocular retention time and improving the tacrolimus amount into the cornea. The cationic liposomes notably prolonged the ocular retention time of eye drops, leading to an increased tacrolimus concentration in the ocular surface. The tacrolimus liposomes were also demonstrated to reduce reactive oxygen species and dry eye-related inflammation factors. The use of drug-loaded cationic liposomes is a good formulation in the treatment of ocular disease; the improved ocular retention time and biocompatibility give the tremendous scope for application in the treatment of ocular disease, with further work in the area recommended.